Analisis Human Error pada Proses Benang Open End di PT. Lotus Indah Textile Industries - Rita Nurul Andita Putri; Anita Oktaviana Trisna Devi; Yunita Primasanti (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
PT. Lotus Indah Textile Industries, a manufacturing company in the open-end yarn spinning sector, faces significant issues related to defective products in its production process. This study aims to identify the level of human error among open-end machine operators and analyze the root causes of these errors. The methods employed include the Human Error Assessment and Reduction Technique (HEART) to calculate the Human Error Probability (HEP), as well as Root Cause Analysis (RCA) with the 5 Whys approach to identify the root problems. Data were collected through observation, interviews, and questionnaires during the period of May to June 2025. The results indicate that the activity of "pushing the full yarn so that it detaches from the holder and moves to the conveyor with the right hand" had the highest HEP value of 0.281996. The main root causes of human error include a lack of focus and accuracy among operators, rushing while working, limited experience, and insufficient training and periodic evaluations of employee effectiveness by the company. The impact of these errors results in defective products such as dirty yarn and rolls that do not meet standards. As an improvement recommendation, the company is advised to conduct periodic evaluations of operator effectiveness after training to enhance productivity and provide feedback, as well as to establish clear procedures for the doffing process of yarn on open-end machines to reduce errors. This study is expected to assist the company in improving operator performance, reducing human error rates, and minimizing defective products.